Haptic industrial robot control and bilateral teleoperation by using a virtual visual interface - Abut, Tayfun; Soyguder, Servet (Institute of Electrical and Electronics Engineers Inc., 2018)
This study attempts to control the movement of industrial robots by using a virtual visual interface. Teleoperation systems that provide information about point or environment that people cannot reach and are one of the important robotic works that include the human-machine interaction technology were used to obtain the necessary data. Robots, as the simulated virtual environment to achieve real behaviors, were found to be important for the identification of damage that may occur during the tests performed by real robots and then in terms of prevention of errors identified in algorithm development stages. The virtual environment was created; variable time delay motion control with teleoperation was performed and applied in the simulation and real-time environment; and the performance results were analysed. © 2018 IEEE.
Sanal bir görsel arayüz kullanarak haptik endüstriyel robot kontrolü ve iki yönlü teleoperasyon
26th IEEE Signal Processing and Communications Applications Conference, SIU 2018 -- 2 May 2018 through 5 May 2018 -- Izmir -- 137780
Keywords: Bilateral teleoperation; Haptic industrial robot; Modified wave variables method; Style; Virtual visual interface